Infrared Thermographic and Ultrasonic Inspection of Randomly-Oriented Short-Natural Fiber-Reinforced Polymeric Composites - Loganathan, Tamil Moli; Sultan, Mohamed Thariq Hameed; Muhammad Amir, Siti Madiha; Jamil, Jeffry; Yusof, Mohd Reusmaazran; Md Shah, Ain Umaira (Frontiers in Materials, 2021)
Non-destructive testing (NDT) is not only primarily concerned with the detection of discontinuities, but also with the mechanical properties. However, the usage of NDT in understanding the mechanical effect that leads to a failure of composites and the damage mechanisms are still not thoroughly studied, as much of the NDT approaches are widely used to maintain the structural integrity to preserve quality assurance. This work aims to investigate the application of infrared thermographic and ultrasonic in evaluating randomly-oriented short-natural-fiber-reinforced phenolic composites. The composites were made from short palm fibers of various sizes between 1.18-0.6mm, 0.6-0.3mm, and less than 0.3mm at 20wt and 40wt%, respectively. The tensile results obtained from the parallel testing of the composites using infrared thermography, where the temperature and time changes on the tested samples were continuously recorded. The peak in the temperature-time graph indicated a macro crack growth and matrix cracking in the form of dissipated energy. Ultrasonic inspection were carried out on the impacted specimens. A scan of the ultrasonic testing on the phenolic composites found presence of a back wall in neat phenolic and was eradicated with fiber reinforcement due to attenuation and energy dissipation. The attenuation coefficient of composites was calculated with the aid of the A-scan. Therefore, it is concluded that ultrasonic inspection on the natural fiber is limited due to the large scattering of wave and energy loss due to attenuation, while infrared thermography is suitable to inspect natural-fiber-reinforced composites when monotonic loadings are applied.